Nitrogen use efficiency and soil fertility as influenced by integrated nitrogen management and foliar spray of iron in groundnut on Typic Ustochrept - PAREEK, N. K.; RAKESH, SHRI (Journal of Soil and Water Conservation, 2021)
A field experiment was conducted at experiment farm, Swami Keshwanand Rajasthan Agricultural University, Bikaner during two consecutive kharif seasons in sandy and slightly alkaline Ustochrepts/ Entisols to study the effect of integrated use of organic and inorganic source of N in conjunction with Fe on nitrogen use efficiency and soil fertility status of groundnut. Application of FYM @ 15 t ha-1 significantly increased the soil organic carbon content, available N status, available P2O5 status and available K2O status during both the years, respectively. Increasing levels of nitrogen had a tendency of improving the organic carbon content and available N status of soil and decreasing the available P, available K and DTPA extractable iron status of the soil only slightly during both the years. Foliar spray of Fe applied alone or in combination with citric acid had no significant effect on the organic carbon content and available N, P, K and DTPA extractable iron status of the soil after harvest of the crop during both the years. Response of groundnut to applied nitrogen decreased considerably with FYM application and foliar spray of iron alone or applied in integration with citric acid @ 0.1% during both the years and pooled basis while increasing levels of nitrogen decreased the NUE while its application in more number of splits.